Low protein diet influences mineral absorption and utilization in medium-growing yellow-feathered broilers from 1 to 30 days of age - Xiaoran Li; Chong Wang; Shunying Li; Liyang Zhang; Xiudong Liao; Lin Lu (Poultry Science)
Reduced-protein diet can save protein ingredients and reduce nitrogen (N) losses. However, the effect of low protein diet on the mineral uptake and utilization in broilers needs to be explored. The aim of this study was to investigate the effect of low-protein diet on the growth performance, N deposition, mineral contents in serum, tissues and excreta, and the activities and gene expression of related enzymes in tissues of medium-growing yellow-feathered broilers, so as to elucidate the relationship between dietary protein level and the absorption and utilization of minerals in broilers. A total of 72 1-d-old Spotted-Brown male broilers were randomly allotted to 1 of 2 treatments with 6 replicate cages of 6 birds per cage for each treatment. The dietary crude protein (CP) levels for the two treatments were 21 % (the control treatment) and 19 % (low protein treatment), respectively. The experimental period was 30 d. The results showed that no differences (P > 0.05) were detected in average daily gain, average daily feed intake and feed: gain ratio of broilers during 1 to 30 d between the two treatments. However, low protein intake increased (P < 0.05) N retention rate, serum P, Cu and Mn, and excreta Cu, Mn and Zn, and decreased (P < 0.05) liver P and excreta P. In addition, birds fed low protein diet had higher (P < 0.05) manganese superoxide dismutase, and total superoxide dismutase activities in liver, and total antioxidant capacity and malondialdehyde content in heart, and lower (P < 0.05) copper-zinc superoxide dismutase (CuZnSOD) and succinate dehydrogenase activities in liver and CuZnSOD mRNA level in heart. In conclusion, the reduction of dietary CP content from 21 % to 19 % improved N retention, the absorption of P, Cu and Mn, as well as the antioxidant ability of liver and heart, and influenced metabolic utilization of P, Cu, Zn, Fe and Mn in medium-growing yellow-feathered broilers from 1 to 30 d of age.